SAMPLE GEOMETRY AND U UPTAKE IN ARCHAEOLOGICAL TEETH: IMPLICATIONS FOR U-SERIES AND ESR DATING - Pike A.W.G.; Hedges R.E.M. (My University, 2001)
Post-deposition U uptake by bones and teeth is the most significant source of inaccuracy in both U-series and ESR dating. In most cases assumptions about the form of U uptake are required to calculate a date. We have been using the diffusion-adsorption (D-A) model of U uptake to predict the rate of uptake and spatial distribution of U and U-series isotopes in bones, and calculate open-system ages. Here we develop a similar model to predict U uptake in enamel and enamel-dentine systems. We find that the traditional models of U uptake, namely linear and early uptake providing maximum and minimum ages, are not universally applicable. Geochemical changes in the burial environment can lead to leaching or recent accumulation of U. In addition, the geometry of the tooth affects the pattern of U accumulation, with some areas of the enamel showing uptake between early and linear, while other areas of the same tooth may exhibit sublinear (recent) uptake. We show, however, how the measurement of the U and U-series isotope distributions (profiles) for a tooth can be combined to model uptake, and provide more reliable U-series dates or ESR dosimetry.
Keywords: ESR dating